PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI PATRA SEMARANG HOTEL & CONVENTION - Mudrik Mudrik; Andhi supriyadi; Dyah Palupiningtyas; Heru Yulianto; Krisna Tri Argo (LPPM Universitas Sains dan Teknologi Komputer, 2020)
This research was conducted at Patra Semarang Hotel & Convention which aims to analyze and explain the influence of leadership style and organizational culture on employee performance, and to find out which variables are most influential on tourist satisfaction.This research uses quantitative methods with 55 respondents. The validity and reliability test techniques, multiple regression analysis, hypothesis testing through the f test, t test, coefficient of determination and beta coefficient.The results showed that the level of testing was significant and positively influenced by the regression equation, Y = -0.005 X1 + 0.971 X2 and it was proven that the organizational culture variable had the most dominant influence on employee performance with a regression coefficient of 0.971. The conclusion from this study that of the two independent variables, organizational culture is a variable that has a positive effect on employee performance at Patra Semarang Hotel & Convention.